2009
DOI: 10.1051/apido/2009065
|View full text |Cite
|
Sign up to set email alerts
|

Novel lactic acid bacteria inhibitingPaenibacillus larvaein honey bee larvae

Abstract: We evaluated the antagonistic effects of newly identified lactic acid bacteria (LAB) in the genera Lactobacillus and Bifidobacterium, originating from the honey stomach, on the honey bee pathogen, Paenibacillus larvae. We used inhibition assays on agar plates and honey bee larval bioassays to investigate the effects of honey bee LAB on P. larvae growth in vitro and on AFB infection in vivo. The individual LAB phylotypes showed different inhibition properties against P. larvae growth on agar plates, whereas a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
311
1
8

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(333 citation statements)
references
References 31 publications
13
311
1
8
Order By: Relevance
“…Honey bees possess a diverse LAB microbiota in their honey crop, acquired by consuming pollen and nectar and through contact with older bees of the colony. All the extant honey bee species possess Lactobacillus and Bifidobacterium within the crop in biofilms (Vasquez et al, 2012), with potential to inhibit American Foul Brood-causing Paenibacillus larvae growth on agar plate (Forsgren et al, 2009). Especially, Lactobacullus kunkeei is predominantly found in A. laboriosa honey in Nepal (10 8 cfu per gram honey), followed by A. mellifera honey in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Honey bees possess a diverse LAB microbiota in their honey crop, acquired by consuming pollen and nectar and through contact with older bees of the colony. All the extant honey bee species possess Lactobacillus and Bifidobacterium within the crop in biofilms (Vasquez et al, 2012), with potential to inhibit American Foul Brood-causing Paenibacillus larvae growth on agar plate (Forsgren et al, 2009). Especially, Lactobacullus kunkeei is predominantly found in A. laboriosa honey in Nepal (10 8 cfu per gram honey), followed by A. mellifera honey in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…set,^and the latter are generally found in the gut microbiota of social bees (Kaltenpoth 2011;Koch and Schmid-Hempel 2011b;Cariveau et al 2014). Core bacteria dominating the gut of social honeybees and bumblebees have been implicated in beneficial functions such as digestion and protection (Klungness and Peng 1984;Forsgren et al 2010;Vásquez et al 2012;Kwong et al 2014). Multiple conditions have been reported influencing the bacterial gut community, including the environment, host age, habitat, pathogens, and diet (Dillon et al 2010;Evans and Schwarz 2011;Hu et al 2014;Yun et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, some bacterial strains and products of their metabolism have begun to receive special scientific attention. Some studies have reported beneficial effects of microbiota on bees' health (Mattila et al, 2012;Janashia & Alaux, 2016) and undesirable effects particularly on microbial threats (Forsgren et al, 2009;Vásquez et al, 2012;Baffoni et al, 2015;Audisio, 2016). Our study was focused on assessing the effect of bacterial metabolites produced by a LAB (L. johnsonii AJ5) on nutritional parameters, N. ceranae development and performance of A. mellifera colonies.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence of an increase of antimicrobial peptide (AMPs) production induced by honey bee gut bacteria (Evans & Lopez, 2004;Jefferson et al, 2013;Yoshiyama et al 2013;Janashia & Alaux, 2016). Several in vitro trials confirmed the hability of lactobacilli and bifidobacteria to inhibit honey bee pathogens, in particular Paenibacillus larvae, Melissococcus plutonius and Ascosphaera apis (Forsgren et al, 2009;Sabaté et al, 2009;Yoshiyama & Kimura, 2009;Vásquez et al, 2012). Similarly, a reduction in N. ceranae intensity was reported when a Bacillus spp.…”
Section: Introductionmentioning
confidence: 90%